PENGARUH PENGGUNAAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR IPA TERPADU SISWA DI SMP NEGERI 1 PANEI - SALOME RAJAGUKGUK (JURNAL ILMIAH MAKSITEK, 2019)
This study aims to determine the effect of using Numbered Head Together learning model on Integrated Science learning outcomes of class VII students of SMP Negeri 1 Panei. This research was conducted from August to October 2018 at IPanei State Middle School, Simalungun District. Samples taken by cluster random sampling obtained 64 people (two classes) where one class (32 people) as an experimental class were taught with Numbered Head Together learning model and one class (32 people) as a control class taught with conventional models. The data obtained were analyzed using SPSS 21. From the results of the study obtained student learning outcomes with Numbered Head Together (80.62) learning model was better than the conventional model (72.19). From the results of hypothesis testing using the t test at the significance level α = 0.05, obtained tcount (3.30)> t table (2.00), then Ha is accepted, meaning that there is the influence of using Numbered Head Together learning model on Integrated Science learning outcomes VII SMP Negeri 1 Panei. It was concluded that there was an influence on the use of Numbered Head Together learning model on the learning outcomes of Integrated Science in students in class VII of SMP 1 Panei 2018/2019 Academic Year. Learning with the Numbered Head Together model can improve students' Integrated Science learning outcomes in object classification material, so this learning model is one alternative that can be used in planning better Integrated Science learning.